Isolated integrin β3 subunit cytoplasmic domains require membrane anchorage and the NPXY motif to recruit to adhesion complexes but do not discriminate between β1– and β3-positive complexes - Foletti, Alessandro; Alghisi, Gian Carlo; Ponsonnet, Lionel; Rüegg, Curzio (Thrombosis and Haemostasis, 2005)
Integrin adhesion receptors consist of non-covalently linked α and β subunits each of which contains a large extracellular domain, a single transmembrane domain and a short cytoplasmic tail. Engaged integrins recruit to focal structures globally termed adhesion complexes. The cytoplasmic domain of the β subunit is essential for this clustering. β1 and β3 integrins can recruit at distinct cellular locations (i.e. fibrillar adhesions vs focal adhesions, respectively) but it is not clear whether individual β subunit cytoplasmic and transmembrane domains are by themselves sufficient to drive orthotopic targeting to the cognate adhesion complex. To address this question, we expressed fulllength β3 transmembrane anchored cytoplasmic domains and truncated β3 cytoplasmic domains as GFP-fusion constructs and monitored their localization in endothelial cells. Membrane-anchored full-length β3 cytoplasmic domain and a β3 mutant lacking the NXXY motif recruited to adhesion complexes, while β3 mutants lacking the NPXY and NXXY motifs or the transmembrane domain did not. Replacing the natural β subunit transmembrane domain with an unrelated (i.e. HLA-A2 α chain) transmembrane domain significantly reduced recruitment to adhesion complexes. Transmembrane anchored β3 and cytoplasmic domain constructs, however, recruited without discrimination to β1– and β3-rich adhesions complexes. These findings demonstrate that membrane anchorage and the NPXY (but not the NXXY) motif are necessary for β3 cytoplasmic domain recruitment to adhesion complexes and that the natural transmembrane domain actively contributes to this recruitment. The β3 transmembrane and cytoplasmic domains alone are insufficient for orthotopic recruitment to cognate adhesion complexes.
Keywords: Integrin; adhesion complexes; endothelial cell; transmembrane domain